Pseudogenes as Potential Diagnostic, Prognostic and Therapeutic Biomarkers in Colorectal Cancer: A Systematic Review - Ali Asadzadeh; Alireza Zangooie; Parmida Bagheri; Helia Zangooie; Zahra Salehi (Cancer Reports)
ABSTRACT Background Colorectal cancer (CRC) is a leading cause of oncologic death worldwide. Elucidating the molecular mechanisms that underpin its pathogenesis is essential for identifying novel therapeutic targets. Pseudogenes have historically been regarded as non‐functional genomic vestiges but have gained recognition for their contributory roles in the oncogenesis of CRC. Aims This systematic review aims to comprehensively evaluate the current literature regarding the involvement of pseudogenes in CRC, with a focus on their clinical relevance as diagnostic and prognostic biomarkers and their potential as innovative therapeutic targets. Methods and Results We conducted a comprehensive literature search following the PRISMA guidelines across PubMed, SCOPUS, and Web of Science databases. Two reviewers independently carried out the screening of studies and extraction of relevant data. Nineteen studies met the inclusion criteria. These studies highlight pseudogenes' emerging role in colorectal cancer, transitioning from being seen as evolutionary remnants to recognized contributors in tumorigenesis. Key pseudogenes like DUXAP8, SUCLG2P2, and SUMO1P3 are linked to crucial CRC processes such as proliferation, migration, invasion, and angiogenesis. The diagnostic and prognostic potential is found in pseudogenes like MYLKP1 (with SNPs rs12490683 and rs12497343) and POU5F1P1 (SNP rs6983267). Additionally, CDCP1, SUCLG2P2, and MT1DP offer prognostic insights, guiding personalized treatment approaches. Pseudogenes such as CTNNAP1, NMRAL2P, and DUXAP8 show therapeutic potential, advocating for further research into their mechanisms to enhance CRC diagnostics and personalized care. The intricate involvement of pseudogenes in CRC pathogenesis underscores their importance. Conclusion Our review illuminates the promise of pseudogenes as biomarkers and therapeutic targets, indicating a significant step toward the integration of pseudogenes in the future paradigm of precision medicine for CRC.